Pengaruh Edukasi Tentang Perawatan Hipertensi Di Rumah Terhadap Pengetahuan Pasien Hipertensi Di Murni Teguh Memorial Hospital - Silaban, Dian Handayani; Simatupang, Lenny Lusia (Indonesian Trust Nursing Journal, 2025)
Hypertension is a disorder of the blood vessels which results in the supply of oxygen and nutrients carried by the blood being blocked from reaching the body tissues that need it. The body shows a hunger reaction and causes the heart to have to work harder to meet needs. the. If this condition persists for a long time and is not treated immediately, symptoms of high blood pressure will appear. The aim of this study was to determine the effect of education about hypertension treatment at Murni Teguh Memorial Hospital. This type of research is Quantitative with a Quasi-Experimental method with a One Group Pretest Posttest approach, sampling using purposive sampling of 45 people. Data analysis using a paired t-test. The results of this study used a paired t-test (Paired-Samples Test). It was found that there was an influence of education about hypertension treatment with a p-value <0.005. and t count (3.54) > t table (2.09). It is hoped that health services can provide health education about the benefits of education to overcome the problem of hypertension.